A census of penguins and seals on Bouvetøya - Haftorn, Svein; Sømme, Lauritz; Gray, John S (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; pingviner; seler; zoologi

Cold tolerance of alpine, Arctic, and Antarctic Collembola and mites - Sømme, Lauritz (Cryobiology, 1981)
Because of their dominant role in the fauna of alpine, Arctic and Antarctic locations Collembola and mites are of particular interest regarding adaptations to low temperatures. No freezing-tolerant species have been found in these groups of terrestrial arthropods, and it appears that all species depend entirely on supercooling to survive the lower temperatures of their habitats. While summer animals have high supercooling points, an increase in supercooling ability occurs during autumn and early winter, and can be explained as a two-step process. Initially gut content has to be eliminated to avoid heterogeneous nucleation at high subzero temperatures due to foreign nucleating agents. Second, supercooling is further enhanced through accumulation of glycerol or other lowmolecular cryoprotective substances. Further studies are needed on the ability of such animals to avoid inoculative freezing in their microhabitats.
Keywords: Antarktis; entomologi; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

Supercooling in two Antarctic arthropods from Bouvetøya - Sømme, Lauritz (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; kuldetoleranse; leddyr; virvelløse dyr; zoologi